2019
DOI: 10.1021/acs.jproteome.8b00915
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Profiling of Aqueous Humor in Glaucoma Points to Taurine and Spermine Deficiency: Findings from the Eye-D Study

Abstract: We compared the metabolomic profile of aqueous humor from patients with primary open-angle glaucoma (POAG; n = 26) with that of a group of age-and sex-matched non-POAG controls (n = 26), all participants undergoing cataract surgery. Supervised paired partial leastsquares discriminant analysis showed good predictive performance for test sets with a median area under the receiver operating characteristic of 0.89 and a p-value of 0.0087. Twenty-three metabolites allowed discrimination between the two groups. Univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 29 publications
9
71
1
Order By: Relevance
“…Some other studies reported the metabolomics of the aqueous humor in a rat model of POAG using nuclear magnetic resonance [20]. The last investigation described metabolomic profiling of aqueous humor in POAG patients by a standardized targeted metabolomics strategy [18]. Thus, to our knowledge, the present study, is the first that investigates the metabolic profiling of tears in naïve to therapy glaucomatous patients, even if only a small cohort of tear samples were analyzed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Some other studies reported the metabolomics of the aqueous humor in a rat model of POAG using nuclear magnetic resonance [20]. The last investigation described metabolomic profiling of aqueous humor in POAG patients by a standardized targeted metabolomics strategy [18]. Thus, to our knowledge, the present study, is the first that investigates the metabolic profiling of tears in naïve to therapy glaucomatous patients, even if only a small cohort of tear samples were analyzed.…”
Section: Discussionmentioning
confidence: 93%
“…Considering the global incidence of POAG and the great impact of an early stage disease diagnosis on the patient quality of life, screening strategies for early diagnosis and treatment of POAG are highly required [16]. To date, only few studies described the metabolomic profiles in POAG using mass spectrometry [15,17,18]. Many of these studies have been performed on the blood of individuals with POAG.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, also the levels of hydroxyproline, derived from the hydrolysis of collagen [ 93 ] and acetate [ 94 ], the latter correlating with the changes in outflow dynamics, due to either cell loss or the dysfunction of sub-cellular structures, increase in POAG AH.…”
Section: Oxidative Stress and Mitochondria Dysfunctionmentioning
confidence: 99%
“…It has been suggested that taurine supplementation may have a neuroprotective effect in retina [ 199 ]. Accordingly, taurine improved RGC survival in a rat retinal explant exposed to serum deprivation or N-methyl-D-aspartate (NMDA) [ 200 ].…”
Section: Taurinementioning
confidence: 99%